The Influence of Audit Opinions, Management Changes, Audit Fees, Auditor Reputation on Auditor Switching - Muhammad Tandzillah; Iman Waskito (Formosa Journal of Multidisciplinary Research, 2024)
The aim of this research was to prove the influence of audit opinions, management changes, audit fees and auditor reputation on auditor switching. The place where this research was conducted was at IDX (Indonesia Stock Exchange) and analyzed using causal quantitative analysis methods. Then the population selected was 10 companies operating in the mining sector that were registered on IDX. The financial reports of each company were looked at in the last 5 years, namely 2019 to 2023. The results of this research show that audit opinion, management changes, auditor reputation have an effect on auditor switching, then audit fees have a positive and insignificant effect on auditor switching. This can be seen from the t test with a significance value <0.05.